Influence of wood moisture content on modulus of elasticity on tension paralllel to the grain of brasilian species - Faria, Obede Borges [UNESP]; Silva, Diogo Aparecido Lopes; Lahr, Francisco Antonio Rocco; Chahud, Eduardo; Varanda, Luciano Donizete (My University, 2012)
Periodically, when necessary, standard documents are revised in order to analyze inconsistencies and to include considerations according new realities verified. In this sense, aiming to quantify the wood moisture content influence on modulus of elasticity, it was applied tension tests parallel to the grain for six specimens of different strength classes of wood, considering nominal moisture of 12, 20, 25, and 30% in Brazil. The present paper examine the adequacy of the current Brazilian standard ABNT NBR7190:1997, in review, about the adoption of a first degree equation to describe the influence of wood moisture content for timber structures design. It was obtained a new first degree equation which leads to statically equivalent estimations when compared with results by ABNT NBR7190:1997 equation. However, as recommendations it could be maintain the current expression for the next text of the referred document review, without prejudice to statistical significance of the estimates.
Keywords: Timber structures design; Wood moisture content; Modulus of elasticity; Tension parallel to the grain